2022
DOI: 10.3390/met12040573
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Various Plasticity Mechanisms to the Deformation Behavior of Gradient Nanograined FeNi Alloy

Abstract: This paper investigates the deformation behavior of a gradient grained FeNi sample under uniaxial tension using molecular dynamics simulations. The simulated sample consists of five layers with grains of the same size in each layer ranging from 10 to 30 nm. It is shown that the sample plasticity develops through sequential activation of different mechanisms. These are either the generation of certain structural defects, or grain boundary migration, or grain boundary sliding. The onset of plasticity is provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…30 The research findings of Korchuganov et al support the view that the plasticity of gradient-structured materials develops through the sequential activation of different mechanisms. 31 Numerous molecular dynamics simulation studies have shown that heterogeneous gradient nanocrystalline copper exhibits high strength and excellent toughness, which helps in improving and balancing the opposing characteristics of strength and toughness. 32,33 In polycrystalline copper, the gradient of grain size can improve the stability of grain boundaries and enhance the material's plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…30 The research findings of Korchuganov et al support the view that the plasticity of gradient-structured materials develops through the sequential activation of different mechanisms. 31 Numerous molecular dynamics simulation studies have shown that heterogeneous gradient nanocrystalline copper exhibits high strength and excellent toughness, which helps in improving and balancing the opposing characteristics of strength and toughness. 32,33 In polycrystalline copper, the gradient of grain size can improve the stability of grain boundaries and enhance the material's plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Due to small grain sizes and high grain boundary density, plastic deformation in nanocrystalline materials is characterized by a high-flow stress. Plasticity occurs through lattice dislocation slip and grain boundary mechanisms [6][7][8][9]. Lattice dislocation slip is the main plasticity mechanism in nanocrystalline materials with grain sizes ranging from r c to 100 nm, where r c is the threshold grain size lying in the range of 10-30 nm for different materials and structures.…”
Section: Introductionmentioning
confidence: 99%
“…Computer simulations are widely used to study the deformation mechanisms of gradient-grained metallic materials. It is believed that the relationship between the gradientgrained structure and deformation mechanisms at the microscopic level can be most effectively modeled using the molecular dynamics method [8,9,[36][37][38][39][40][41][42][43][44]. Earlier, we numerically studied the deformation behavior of a gradient-grained FeNi sample under uniaxial tension [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable study is currently given to heterogeneous metallic materials with a gradient grained structure, combining high strength and fracture toughness [23][24][25]. The calculation results showed that a higher grain size gradient improves the strength of materials [25].…”
Section: Introductionmentioning
confidence: 99%